Long-Acting Growth Hormone Therapy in Pediatric Growth Hormone Deficiency: A Consensus Statement. - Maniatis, Aristides; Cutfield, Wayne; Dattani, Mehul; Deal, Cheri; Collett-Solberg, Paulo Ferrez; Horikawa, Reiko; Maghnie, Mohamad; Miller, Bradley S.; Polak, Michel; Sävendahl, Lars; Wölfle, Joachim (Journal of Clinical Endocrinology and Metabolism, 2025)
CONTEXT: Several long-acting growth hormone (LAGH) therapies have recently become available, but guidance on their usage in children with growth hormone (GH) deficiency is limited. METHODS: International experts in pediatric endocrinology were invited to join a consensus group based on their expertise in treating children with daily GH and LAGH. The group comprised 11 experts from 10 countries across the world. Online group meetings were held in February to March 2024 followed by a 1-day in-person meeting in May 2024 to finalize the consensus recommendations. A targeted literature search approach was used to identify and share evidence ahead of the meetings. Formulations considered were limited to those with international populations in phase III pivotal trials and regulatory approvals in multiple countries. EVIDENCE SYNTHESIS: Topics covered include patient selection and preference, dose adjustment, initiating and switching therapies, administration, adherence and missed doses, practical considerations, and knowledge gaps. LAGH formulations offer a potential advantage over daily GH injections for children with GH deficiency in terms of reduced injection frequency and treatment burden; this may also be associated with improved adherence and treatment outcomes over time. However, data on LAGH in pediatric GH deficiency are mostly limited to clinical trials, and long-term, real-world data are currently lacking. CONCLUSION: This article provides an international consensus on the use of LAGH therapy in children with GH deficiency to guide practitioners when considering these new treatment options for their patients. Long-term data are needed to fill current data gaps and allow the creation of comprehensive evidence-based recommendations.
EVALuna2:586369